Implementation of Metacognitive Strategies on Students' Ability to Read English Texts (Jurnal Sustainable, 2023)
Reading is one of the crucial language skills for learners, especially when they are learning English. English learners can usually read texts well, but many of them cannot understand the content of the text. This study aims to determine how to implement metacognitive strategies to learn reading skills. Results showed that students had a good awareness of metacognitive reading strategies. However, it did not affect students' reading comprehension test results much. This is because several other factors, such as interest, background knowledge of students, and teachers' role, also significantly influence students' reading comprehension. This study used a case study approach to its analysis. This research demonstrates the efficacy of self-planning, self-monitoring, and self-evaluation as three phases of metacognitive strategy execution. These steps are accomplished via friendly conversation with the pupils. Five pupils in particular shown exceptional levels of motivation, success, self-awareness, and independence in their reading comprehension and other academic endeavours.